Respostas
respondido por:
0
Utiliza-se o teorema de bhaskara.
X=-b+- √b^{2}-4.a.c
-----------------------
2.a
X= 10+-√100-100
-------------------------
2.1
X= 5
X=-b+- √b^{2}-4.a.c
-----------------------
2.a
X= 10+-√100-100
-------------------------
2.1
X= 5
respondido por:
0
a= 1 b= -10 c= 25
Δ = b2−4ac
Δ = (-10)2−4*1*25
Δ = 100-100
Δ = 0
-b ± √Δ - (-10) ± √0 10 ± 0
x = -------------- => x = -------------------- => x = -----------
2*a 2 * 1 2
x' = 5
x'' = 5
S = {5, 5}, as raízes são iguais. É isso que acontece quando o DELTA é igual a zero.
Δ = b2−4ac
Δ = (-10)2−4*1*25
Δ = 100-100
Δ = 0
-b ± √Δ - (-10) ± √0 10 ± 0
x = -------------- => x = -------------------- => x = -----------
2*a 2 * 1 2
x' = 5
x'' = 5
S = {5, 5}, as raízes são iguais. É isso que acontece quando o DELTA é igual a zero.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás